Performance Comparative Analysis of Sharia Mutual Funds and Conventional Mutual Funds - Nursanita; Pratiwi, Willy Yani (SAN Scientific, 2023)
This study aims to compare the performance assessment of Islamic and conventional mutual funds for 2017-2021. This study uses quantitative research, which analyzed the performance of Islamic and conventional mutual funds for 2017-2021. This study relies on secondary data collected from the official website of the Financial Services Authority (OJK). The research compares the performance of Islamic stock mutual funds, mixed mutual funds (comprising both Islamic and conventional funds), and mixed conventional mutual funds using the Sharpe, Treynor, and Jensen methods. Among these methods, the Sharpe method stands out as providing a superior performance evaluation compared to Treynor and Jensen. Both Islamic and conventional stock mutual funds receive a positive assessment, deemed as